The best of Archie comics starring Betty & Veronica - Doyle, Frank 1917-1996; DeCarlo, Dan 1919-2001; Bolling, Bob 1928- (Archie Comic Publications, 2014)
Over "400 pages of the funniest and most iconic stories of the past 70 years featuring Archie's girl friends Betty and Veronica, hand-selected by Archie creators, editors, fans and historians from 200,000 pages of material"--Amazon.com
"All stories previously published and copyrighted by Archie Comics Publications ... in magazine form 1944-2017.
"Archie characters created by John L. Goldwater. The likenesses of the original Archie characters were created by Bob Montana.
Keywords: Andrews, Archie / (Fictitious character) / Comic books, strips, etc / Juvenile fiction; Andrews, Archie / (Fictitious character); Teenagers / Comic books, strips, etc / Juvenile fiction; Friendship / Comic books, strips, etc / Juvenile fiction; Man-woman relationships / Comic books, strips, etc / Juvenile fiction; Friendship; Man-woman relationships; Teenagers; Comics (Graphic works); Comic